GLOBALIZATION OF THE MONETARY SYSTEM - Sharov, Oleksandr (Journal of European Economy, 2017)
The article disputes on future development of the international monetary system under conditions of modern globalization. The author asserts that globalization is an objective process, and thus, the international monetary system continues its logical development from the universal money commodity equivalent (gold) through multiple reserve (international) currencies back to the world money of higher order. The intermediate stage of this process can be the creation of target currency zones with leading currencies, one example of which is the single European currency – the Euro. In this context, the question about further development of monetary systems of separate countries (including Ukraine) takes on special importance.